Impact of Compensation to Employee Retention of Mega Jug Phils. Inc in Malabon City: A Basis for Improving Employee Retention Program: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Nowadays, taking care of the welfare of employees is very important in order to ensure theydo hard work toward organizational goals. The aim of this study is to establish the impact ofcompensation on employee retention. The objective of this research is, firstly, to evaluate thelevel of employee retention. Secondly, this research examines the relationship betweencompensation and employee retention. Lastly, determine the effect of the compensation onemployee retention. This research is carried out at Bestlink College of the Philippines.Based on the result, the researchers conclude that there is no significant relationshipbetween compensation and retention. Based on the results presented, the researchers cameup with the following recommendations such as open communication between employeesand management. Hold regular meetings. The employer should keep in mind the EmployeeCompensation strategy depending on the age of the employees. Employers can conductemployee surveys to get feedback on the current compensation package. A transparent paypolicy can also help boost employee morale and trust in management, showing the companycompensates its employees fairly, gives at least one jug additional for referral commission,Keeps giving the proper benefits for employees, and lastly, keeps giving the best paystructure for employees.
Keywords: Business Administration